Current control options and a way towards risk-based control of Toxoplasma gondii in the meat chain. (April 2023) - Kuruca, Ljiljana; Belluco, Simone; Vieira-Pinto, Madalena; Antic, Dragan; Blagojevic, Bojan
Abstract: Toxoplasma gondii is a zoonotic protozoan with a wide range of hosts and cosmopolitan distribution. Due to its impact on human and animal health, as well as related economic losses, T. gondii is considered as one of the most significant foodborne pathogens nowadays. Consumption of raw or undercooked meat is a well known risk factor for human infection. However, there is no legislation regarding control of T. gondii in the meat chain, and current meat safety assurance systems (MSAS) have little control over this parasite. Traditional meat inspection is not capable of detecting microscopic cysts of T. gondii in the tissues of slaughter animals, and available laboratory tests are still not sufficiently sensitive or specific to detect infection in individual carcasses. Possible solutions for overcoming these challenges and gaining a higher level of control over T. gondii in the meat chain come in the form of a risk-based meat safety assurance system (RB-MSAS) that incorporates risk-categorisation of farms and targeted interventions, as well as education of all interested parties. Highlights: Toxoplasma gondii is one of the highest public health burden hazards. Meatborne transmission of T. gondii contributes significantly to human infection. Current meat control system is not effective against T. gondii . Risk-based meat safety assurance system offers an appropriate control of the hazard. RB-MSAS should be complemented by education of the general public.